Pengaruh Leverage , Profitabilitas, Dan Likuiditas Terhadap Kebijakan Dividen Pada Perusahaan Sektor Industrial Goods Yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2023 - Anjelita, Dhea; Zuraidah; Syahrul Maulidi (Jurnal Sains dan Ilmu Terapan, 2025)
The purpose of this study is to examine the simultaneous and partial effects of Leverage , Profitability, and Liquidity on Dividend Policy in Industrial Goods Sector companies listed on the Indonesia Stock Exchange. This research employs a quantitative method. The population of this study consisted of 33 samples of financial reports from Industrial Goods Sector companies listed on the Indonesia Stock Exchange. The research subjects were Industrial Goods Sector companies listed on the Indonesia Stock Exchange. The data analysis technique used was multiple linear regression analysis. The data used in this study were secondary data. The results indicate that Leverage has a partial positive effect on Dividend Policy in Industrial Goods Sector companies listed on the Indonesia Stock Exchange. Profitability has a partial positive effect on Dividend Policy in Industrial Goods Sector companies listed on the Indonesia Stock Exchange. Liquidity has a partial negative effect on Dividend Policy in Industrial Goods Sector companies listed on the Indonesia Stock Exchange. Leverage